Competing bubble formation mechanisms in rigid polyurethane foaming. (16th July 2021) - Brondi, Cosimo; Di Maio, Ernesto; Bertucelli, Luigi; Parenti, Vanni; Mosciatti, Thomas
Abstract: This study investigates the influence of air bubbles inclusion on the foaming of water blown and water-pentane blown rigid polyurethane and polyisocyanurate foams. It was observed that, when a large number of air bubbles were included in the reacting system during the mixing stage (fast mixing), no further bubble nucleation from water reaction or pentane evaporation occurred. In this case, foam morphology was solely dictated by the mixing stage and by later bubble coarsening. Instead, when no air bubbles were included during mixing (slow mixing), nucleation of new bubbles from CO2 (from water-isocyanate reaction) and pentane was observed. Furthermore, both bubble coalescence and Ostwald ripening were observed as mechanisms responsible for the foam morphology coarsening, the latter being less effective in the case of polyisocyanurate foams. Graphical abstract: Image 1 Highlights: An optical setup allows for the in-situ monitoring of the foaming process of reacting thermosetting polymers. Nucleation of new bubbles was detected in absence of pre-existing air bubbles from aeration. Nucleation of new bubbles was not observed in the case of an aerated mixture. In PU, coalescence in combination with OR affected the foaming stage I, while OR affected the stage II. In PIR, coalescence induces cell coarsening during the foaming stage I, while OR affected the stage II.